Edukasi Pengelolaan Keuangan Sederhana Sebagai Upaya Peningkatan Literasi Keuangan Rumah Tangga Ibu-Ibu PKK di Dusun Tawang - Wulan Aryanti; Agung Prasetiyo; Andara Verlieta Dewi; Ananda Amelia Apri; Saifudin (Yayasan Al-Afif, 2026)
This study aims to improve household financial literacy through simple financial management education for the Family Welfare Movement (PKK) group in Tawang Hamlet, Samirono Village, Getasan District, Semarang Regency, emphasizing the link between financial education and community empowerment. The research method was implemented in three stages: an initial survey, educational program implementation, and post-activity evaluation. The results showed an increase in participants' understanding of the basic concepts of financial literacy, their ability to prepare a monthly budget using the 50/30/20 method, and behavioral changes towards more rational and wise financial management. The active participation and high enthusiasm of PKK members are indicators of the program's success, which not only improves individual capacity but also strengthens social cohesion and supports the community empowerment process. However, this study is still limited to a local scale with a relatively small number of participants, so further research with a wider scope and sample is needed to strengthen the generalizability of the findings.